Open OnDemand: State of the platform, project, and the future. (3rd December 2020) - Chalker, Alan; Franz, Eric; Rodgers, Morgan; Dockendorf, Trey; Johnson, Doug; Sajdak, Doris; White, Joseph P.; Plessinger, Benjamin D.; Zia, Mohammad; Gallo, Steven M.; Settlage, Robert E.; Hudak, David E.
Summary: High performance computing (HPC) has led to remarkable advances in science and engineering and has become an indispensable tool for research. Unfortunately, HPC use and adoption by many researchers is often hindered by the complex way these resources are accessed. Indeed, while the web has become the dominant access mechanism for remote computing services in virtually every computing area, HPC is a notable exception. Open OnDemand is an open source project negating this trend by providing web‐based access to HPC resources ( https://openondemand.org ). This article describes the challenges to adoption and other lessons learned over the 3‐year project that may be relevant to other science gateway projects. We end with a description of future plans the project team has during the Open OnDemand 2.0 project including specific developments in machine learning and GPU monitoring.